2019
DOI: 10.1002/aur.2256
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Social Story Intervention in Training Toothbrushing Skills Among Special‐Care Children With and Without Autism

Abstract: Toothbrushing is a routine practice for oral hygiene maintenance. It is also a challenging task for young children with special care needs. In this study, social stories were employed to teach toothbrushing skills for preschool children with special needs. Those children were recruited from the Special Child Care Centers, including 87 children with autism and 94 children without autism. A validated toothbrushing social story was used to demonstrate the toothbrushing procedure for all the recruited children. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Studies selected were divided into two groups according to their primary outcome. In the first group, articles that investigated the effectiveness of visual pedagogy in improving oral hygiene skills in children with ASDs were included [14][15][16][17][18][19][20][21][22]. In the second group, articles that investigated the effectiveness of visual pedagogy in improving the patient's cooperation during dental care were included [4,[23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Data Collection Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies selected were divided into two groups according to their primary outcome. In the first group, articles that investigated the effectiveness of visual pedagogy in improving oral hygiene skills in children with ASDs were included [14][15][16][17][18][19][20][21][22]. In the second group, articles that investigated the effectiveness of visual pedagogy in improving the patient's cooperation during dental care were included [4,[23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Data Collection Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…Twenty-three studies were finally included in this systematic review: nine studies concerned tooth brushing and oral hygiene skills in children with ASDs and 14 studies concerned their cooperation during dental procedures (Figure 1) [4,. The majority of the papers included (21 studies) were published in the last decade, with 10 papers published from 2018 to 2020 [14,16,17,19,[21][22][23]26,28,32] (Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with sub-average social skills were less likely to follow the instructions given by the caregiver, and they were likely to brush their teeth with improper toothbrushing techniques. If children brushed their teeth with uneven strokes, their toothbrush bristles could be matted or splayed quickly [ 11 ].The prior study also revealed that children with low social skills showed poorer toothbrushing performance than their peers, and toothbrushing trainings in early childhood were recommended for children with special care needs [ 17 , 18 ]. The design of toothbrushes could also influence the deterioration levels of toothbrushes [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%